Farklı kaide materyallerine mikrobiyal tutunmanın değerlendirilmesi - Evşen Tamam (Cumhuriyet University, 2014)
ABSTRACTObjective: The purpose of this study was to compare the different types of  microorganism accumulation of polymethylmetacrilate (PMMA) and cobalt chrome (Co-Cr) denture base.Materials and Methods: Disks were prepared at 10 mm diameter and 1.5 mm thickness with heat cured PMMA and CO-Cr alloy (n=10). Candida albicans and Staphylococcus epidermidis microorganisms were investigated in this study. Acrylic resin and metal alloy specimens were kept in microorganism cultures including 5´ 10-6 colony for ml, for 48 hours at 37ºC. After 48 hours the specimens that were contaminated with microorganisms, were taken off from the tubes and the microorganisms which were loosely attracted were removed Specimens were inocubated at 37°C for 1 day and colonies were calculated after inocubation. Statistical analyses were done with Kolmogorov- Smirnov Z Test and one-way ANOVA (a=0.05).Results: Candida albicans colony calculation were between, 224- 342 col/ml for acrylic specimens and 110-176 col/ml for Co-Cr metal alloys. Staphlococcus epidermidis colony calculation were between 176-274 col/ml for acrylic specimens and 70-144 col/ml for Co-Cr metal alloys. According the results of the statistical evaluation, Candida albicans were accumulated both acrylic and Co-Cr metal alloys' test groupsps and this difference was found statistically significant. (a=0.05).Conclusion: It should be considered that complete dentures with metal base could be an important treatment alternative for treating edentulous patients.